2018
DOI: 10.1007/s00415-018-9016-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in Alzheimer’s disease and mild cognitive impairment

Abstract: Research utilizing magnetic resonance imaging (MRI) has been crucial to the understanding of the neuropathological mechanisms behind and clinical identification of Alzheimer's disease (AD) and mild cognitive impairment (MCI). MRI modalities show patterns of brain damage that discriminate AD from other brain illnesses and brain abnormalities that are associated with risk of conversion to AD from MCI and other behavioural outcomes. This review discusses the application of various MRI techniques to and their clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
179
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(201 citation statements)
references
References 77 publications
4
179
0
1
Order By: Relevance
“…Parameters of water diffusion in white matter derived from diffusion-weighted imaging (DWI), such as fractional anisotropy (FA), mean, axial, and radial diffusivity (MD, AD, and RD) are well-established markers of normal brain maturation (1)(2)(3)(4)(5) and ageing (6)(7)(8)(9)(10)(11)(12) and have been proposed as potential tools for the investigation of various brain disorders (13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Parameters of water diffusion in white matter derived from diffusion-weighted imaging (DWI), such as fractional anisotropy (FA), mean, axial, and radial diffusivity (MD, AD, and RD) are well-established markers of normal brain maturation (1)(2)(3)(4)(5) and ageing (6)(7)(8)(9)(10)(11)(12) and have been proposed as potential tools for the investigation of various brain disorders (13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is the most common chronic neurodegenerative disease, characterized by a gradual decline in cognitive function that leads to problems in daily life (Gutierrez and Vitorica, 2018). The common diagnostic methods for AD have some disadvantages: ordinary brain magnetic resonance imaging (MRI)can only minimally reveal brain atrophy at the early stage (Chandra et al, 2019), and examining pathological biomarker levels (i.e.,amyloid β-protein and tau protein) in the cerebrospinal fluid (CSF) through lumbar puncture is difficult to routinely apply, given the invasivity of the procedure (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse tensor imaging (DTI) was used to investigate neurological disease, such as epilepsy, Parkinson’s disease and Alzheimer’s disease. 19 21 Marqués-Iturria et al used DTI to reconstruct and compare obese (n=31) and non-obese (n=32) subjects’ brain reward networks based on white matter volume and microstructure, the authors reported that obese subjects displayed a lower number of fibers and decreased integrity of connections in addition to reduced network clustering strength among the orbitofrontal cortex and striatum nuclei including the accumbens, caudate, and putamen when compared with non-obese subjects. 22 In a separate study, Kullmann et al used DTI and multiparametric mapping to examine the effect of increasing BMI among lean, overweight, and obese subjects on brain white matter.…”
Section: Introductionmentioning
confidence: 99%